Granting assimilation and integration rights to prisoners (adults and children) in the center of the pandemic Covid-19 - Muhammad Nuh; Evi Retno Wulan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Nowadays the community is not only researched by the spread of Corona viruses, but the public must also be introof from crime action. Crime phenomenon amid pandemic conditions, the culprit is mostly an inmate who get an assimilation program. The assimilation Program itself is issued by the Government through the Ministry of Justice and Human rights. How not worried, the policy precisely raises the middle of the community, in the current conditions that are panicked with social insecurity. This is due to lack of supervision from the manager of the prison in the assimilation program so that many inmates who are not well qualified can get assimilation program, then the current economic conditions that carut-marut amid the pandemic Corona virus or Covid-19, unemployment is a lot, life is difficult so that the potential criminologinya very large. Then no wonder a number of prisoners are revisit. Based on the background above, this proposal can be formulated as follows: 1. is the granting of assimilation and integration rights to the convicts (adult and child) in the middle of the Covid-19 pandemic already in accordance with the legislation? 2. Is it necessary to add new rules governing assimilation and integration rights in the middle of the Covid-19 pandemic? A) This research aims to know and analyze from the side of regulation, especially Permenkumham No. 10 year 2020 on the release of convicts and children in the middle of the Covid-19 pandemic, in order to prevent the transmission of Covid-19 in correctional institution. B) The second purpose of the study is to know and analyze the government needs to issue specific regulations related to assimilation and integration rights in the midst of pandemic Covid-19.